Mapeamento do suicídio no estado do Espírito Santo: uma análise espacial do início do século XXI - Freitas, Marcone Henrique de (2023)
Introduction: Suicide is a phenomenon that has highly complex factors and that, in recent decades, due to its constant growth in terms of morbidity and mortality levels, suicide has come to represent a serious problem for Public Health. Objective: to analyze the spatial distribution of suicide cases in the state of Espírito Santo between 2001 and 2019. Result: In the analyzed period, 3102 deaths from suicide were recorded in the state, which responded to a standardized average rate of 5.25 deaths per 100,000 inhabitants. The results showed a predominance of deaths in the male population, aged between 30 and 39 years and place of occurrence in households. The most used means was hanging, followed by self-intoxication for both sexes. In addition, the microregions of Santa Tereza and Afonso Cláudio had the highest rates over the analyzed period. Conclusion: Through the results obtained, it becomes evident that the epidemiological profile of suicides has a defined pattern, however, with variations depending on the micro-region. In addition, the study identified a concentration of the highest rates in the central micro-regions, which may indirectly contribute to guiding future campaigns to value life and/or actions to combat and protect against suicide.